Sugar reduction without compromising sensory perception. An impossible dream?. Issue 14 (6th August 2019) - Hutchings, Scott C.; Low, Julia Y. Q.; Keast, Russell S. J.
ABSTRACT: Sugar reduction is a major technical challenge for the food industry to address in response to public health concerns regarding the amount of added sugars in foods. This paper reviews sweet taste perception, sensory methods to evaluate sugar reduction and the merits of different techniques available to reduce sugar content. The use of sugar substitutes (non-nutritive sweeteners, sugar alcohols, and fibres) can achieve the greatest magnitude of sugar and energy reduction, however bitter side tastes and varying temporal sweet profiles are common issues. The use of multisensory integration principles (particularly aroma) can be an effective approach to reduce sugar content, however the magnitude of sugar reduction is small. Innovation in food structure (modifying the sucrose distribution, serum release and fracture mechanics) offers a new way to reduce sugar without significant changes in food composition, however may be difficult to implement in food produced on a large scale. Gradual sugar reduction presents difficulties for food companies from a sales perspective if acceptability is compromised. Ultimately, a holistic approach where food manufacturers integrate a range of these techniques is likely to provide the best progress. However, substantial reduction of sugar in processed foods without compromising sensory properties may be an impossible dream.